2020
DOI: 10.1002/pat.4799
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardancy and smoke suppression of silicone foams with microcapsulated aluminum hypophosphite and zinc borate

Abstract: The flame‐retardant microcapsules were successfully fabricated with an aluminum hypophosphite (AHP) core. Fourier transform infrared (FTIR) and X‐ray photoelectron spectroscopy (XPS) were used to verify that AHP was encapsulated in the microcapsules, and thermogravimetry analysis showed that microencapsulated AHP (MAHP) possessed higher thermal stability than that of AHP. Then, a flame‐retardant and smoke suppression system for silicone foams (SiFs) was obtained through a synergistic effect of MAHP and zinc bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 44 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…The peak of CO generation in RPUF-1 was about 0.03 g/ s, while the yield of RPUF-6 was significantly increased with the addition of AHP, which may because the oxidation of phosphine generated by AHP resulted in the hypoxic atmosphere and inhibited full oxidation of carbon element in RPUF. 40 When ITs was combined with AHP and added into RPUF, RPUF-4 possessed significantly decreased CO yield compared with RPUF-6, implying excellent toxicity reduction performance of ITs.…”
Section: Combustion Behavior Of Rpuf and Fr-rpuf Compositesmentioning
confidence: 95%
“…The peak of CO generation in RPUF-1 was about 0.03 g/ s, while the yield of RPUF-6 was significantly increased with the addition of AHP, which may because the oxidation of phosphine generated by AHP resulted in the hypoxic atmosphere and inhibited full oxidation of carbon element in RPUF. 40 When ITs was combined with AHP and added into RPUF, RPUF-4 possessed significantly decreased CO yield compared with RPUF-6, implying excellent toxicity reduction performance of ITs.…”
Section: Combustion Behavior Of Rpuf and Fr-rpuf Compositesmentioning
confidence: 95%
“…A comparison of data from other literature on smoke‐suppression strategies of RPUF is listed in Table S1. Among those strategies, boron compounds such as zinc borate (ZB), 20,21 boron phosphate (BP) 22,23 and so on were often chosen to be utilized in RPUFs. ZB is a multifunctional flame retardant containing different proportions of zinc and boric acid oxides 24 .…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Hu et al 19 reported the combining effect of ATH, ammonium polyphosphate, and mica to improve the flame retardancy and fire prevention of silicone rubber ceramifying composites. Kang et al 20 studied a synergistic effect between microcapsulated aluminum hypophosphite and zine borate used in silicone foams, and found it exerted excellent smoke suppression and flame retardant properties.…”
Section: Introductionmentioning
confidence: 99%